2015
DOI: 10.1038/bjc.2015.228
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of survivin and MAOA synergistically impairs growth of PTEN-negative prostate cancer

Abstract: Background:Survivin and monoamine oxidase A (MAOA) levels are elevated in prostate cancer (PCa) compared to normal prostate glands. However, the relationship between survivin and MAOA in PCa is unclear.Methods:We examined MAOA expression in the prostate lobes of a conditional PTEN-deficient mouse model mirroring human PCa, with or without survivin knockout. We also silenced one gene at a time and examined the expression of the other. We further evaluated the combination of MAOA inhibitors and survivin suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…MAOA activity was found to be significant increased (p<0.05) in CSF of patients with acute lymphoblastic leukemia compared with control group as shown in tables (2) and (3) in both sexes for all age groups, this result was in agreement with other reports [27,28] who found evaluated levels of MAO in prostate cancer patients.…”
Section: -Monoamine Oxidase a (Maoa)supporting
confidence: 91%
“…MAOA activity was found to be significant increased (p<0.05) in CSF of patients with acute lymphoblastic leukemia compared with control group as shown in tables (2) and (3) in both sexes for all age groups, this result was in agreement with other reports [27,28] who found evaluated levels of MAO in prostate cancer patients.…”
Section: -Monoamine Oxidase a (Maoa)supporting
confidence: 91%
“…Pargyline has been described to have only slight selectivity for MAO-B (Fuller & Hemrick, 1978). In contrast to MAO-A, MAO-B is expressed in normal prostate tissue and its levels are substantially reduced in PCa tissue (Xu et al, 2015).…”
Section: Other Diseasesmentioning
confidence: 99%
“…MAO inhibitors may also be relevant to other conditions, and are thus under investigation as therapies for Alzheimer's disease, certain types of cancer and age-related impairment of cardiac function. In Alzheimer's disease, MAO inhibitors may reverse amyloid ÎČ peptide (AÎČ) pathology and improve cognitive deficits [21], while MAO-A inhibitors acting synergistically with survivin suppressants, may inhibit prostate cancer cell growth, migration and invasion [22,23]. Based on the observation that hydrogen peroxide produced by MAO-A in the heart increases with age in rats, it has been suggested that MAO-A inhibitors may slow age-related impairment of cardiac function by reducing hydrogen peroxidemediated cardiac cellular degeneration [24].…”
Section: Introductionmentioning
confidence: 99%